A corpus analysis of rubato in Bach's C major prelude, WTC I - Benadon, Fernando; Zanette, Damian Horacio (Royal Northern College of Music, 2015)
Fil: Zanette, Damian Horacio. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina